Nanotheranostics With the Combination of Improved Targeting, Therapeutic Effects, and Molecular Imaging - Peng, Shin-Lei; Lai, Chih-Ho; Chu, Pei-Yi; Hsieh, Jer-Tsong; Tseng, Yen-Chun; Chiu, Shao-Chieh; Lin, Yu-Hsin (Frontiers in Bioengineering and Biotechnology, 2020)
There is an increasing interest in the design of targeted carrier systems with combined therapeutic and diagnostic modalities. Therapeutic modalities targeting tumors with single ligand-based targeting nanocarriers are insufficient for proficient delivery and for targeting two different surface receptors that are overexpressed in cancer cells. Here, we evaluated an activated nanoparticle delivery system comprising fucoidan/hyaluronic acid to improve therapeutic efficacy. The system comprised polyethylene glycol-gelatin-encapsulated epigallocatechin gallate (EGCG), poly (D,L-lactide-co-glycolide; PLGA), and stable iron oxide nanoparticles (IOs). The latter enables targeting of prostate cancers in their molecular images. We demonstrate the transfer of nanoparticles and their entry into prostate cancer cells through ligand-specific recognition. This system may prove the benefits of drug delivery that enhances the inhibition of cell growth through apoptosis induction. Moreover, the improved targeting of nanotheranostics significantly suppressed orthotopic prostate tumor growth and more accurately targeted tumors compared with systemic combination therapy. In the presence of nanoparticles with iron oxides, the hypointensity of the prostate tumor was visualized on a T2-weignted magnetic resonance image. The diagnostic ability of this system was demonstrated by accumulating fluorescent nanoparticles in the prostate tumor from the in vivo imaging system, computed tomography. It is suggested that theranostic nanoparticles combined with a molecular imaging system can be a promising cancer therapy in the future.